Effective communication between doctor and patient using method of neurolinguistic programming: Komunikasi yang efektif antara dokter dan pasien menggunakan metode neurolingustic programming - Ridwan Auwen (Makassar Dental Journal PDGI Makassar, 2020)
Effective communication between doctors and patients is one of the most important competencies and must be mastered by doctors. Communication competence determines successful in helping to resolve patient health. Effective communication can reduce patient doubt, and increase patient compliance. Doctors and patients alike benefit fromsharing in close relationships. Each party feels understood. The patient feels safe and protected if the doctor who handles it does the best for his patient. When connected to each other, the doctor can understand and react better to changes in behavior and attention to patients at all times. Effective communication between doctors and patients is needed to obtain optimal results, in the form of health problems that can be resolved and the recovery of patients. Neurolingustic programming (NLP) is a process of change by intervening(programming)onprogramsinthemind(neurons)usinglanguage.MedialanguageisusedpredominantlyinNLP because the intervention process is essentially a process of communication between parts (parts) within us so that it is aligned with the direction of change we want. Because of the close connection between the mind and this language, the neuron and linguistic words are always written in a neurolinguistic way.